Digital Biomarkers and Medical Algorithms in the Serbian Healthcare Ecosystem: A Comparative Analysis of Knowledge, Attitudes, Practice and Economic Valuation Among Key Healthcare Stakeholders: Digital Biomarkers and Medical Algorithms in Serbian Healthcare System - Obradović, Dragiša; Kralj, Đorđe; Milošević Georgiev, Andrijana; Lakić, Dragana (Journal of Medical Biochemistry, 2026)
Background: Digital healthcare transformation, characterized by digital biomarkers and medical algorithms emergence promises to redefine healthcare system. However, successful implementation relies on acceptance, readiness and economic valuation of key stakeholders as biochemists and clinicians. This study provides first analysis of attitudes, practices, knowledge and economic valuation around digital health diagnostics with specific focus on two sub-cohorts - Biochemists (Medical/Clinical) and Clinicians (Pathologists/Gastroenterologists) as implementation frontrunners. Methods: A cross-sectional survey was conducted with a cohort of 105 healthcare professionals from 53 prominent healthcare institutions. The study used a structured instrument for analysis of digital competencies, perceived benefits and potential risks. A Contingent Valuation Method was employed to determine Willingness to Pay for digital medical solutions. Results: The cohort exhibited high digital literacy level (4.6 out of 5). Biochemists, grounded in analytical validation, expressed greater caution regarding clinical relevance and data privacy. Conversely, Clinicians, driven by the need for diagnostic decision support, demonstrated caution towards finance topics. The analysis revealed optimal price point at €65.9 ± 75.56 (95% CI: €41.2 – €90.6). There is no significant difference between sub-cohorts (p = 0.89). While more than 75% of participants believed digital biomarkers would yield systemic financial savings, 74% were unaware of the existing regulatory frameworks. Conclusions: Serbian healthcare community possesses robust digital foundation. Biochemists view digital medical solutions as analytical solutions requiring validation, while clinicians view them as solutions for diagnostic ambiguity. Establishing national working group on "Digital Diagnostics" to develop guidelines for the validation and to develop reimbursement codes is crucially needed.